The spectrum-efficacy correlation of Kai-Xin-San for cognition of Aβ42 transgenic Drosophila and verification of its active ingredients - Wu, Jinfu; Sun, Hang; Zhao, Yiyang; Lian, Lian; Bian, Hongsheng; Guo, Yong; Li, Dan; Huang, Lili (Frontiers in Pharmacology, 2025)
IntroductionThis study aims to establish the fingerprint spectra of Kai-Xin-San (KXS) and investigate its spectrum-effect relationship in treating Alzheimer’s disease (AD).MethodsInitially, the fingerprints of 15 batches of KXS were established and analyzed using HPLC, with the method’s precision, stability, and repeatability thoroughly evaluated. Subsequently, the effects of the 15 batches of KXS were assessed in an olfactory escape memory experiment, utilizing Aβ42 transgenic drosophila as a model. Finally, the spectrum-effect relationship between the KXS fingerprint and memory improvement was analyzed, with the active ingredients subjected to validation testing.ResultsThe results identified seventeen common peaks in the fingerprint, and eight active components were determined: polygalaxanthone III, 3-6-disinapoylsucrose, ginsenoside Rg1, ginsenoside Rb1, β-asarone, α-asarone, dehydrotumulosic acid, and dehydropachymic acid. Treatment with KXS (1%, for 4 days) significantly enhanced the performance index of Aβ42 flies in the olfactory experiment. Both spectrum-effect analysis and validation tests indicated that polygalaxanthone III, ginsenoside Rg1, ginsenoside Rb1, β-asarone, and α-asarone were positively correlated with the performance index and improved the performance index in the olfactory experiment. The HPLC fingerprint method for KXS demonstrated excellent precision, accuracy, and reproducibility, making it suitable for quality evaluation and control of KXS. Polygalaxanthone III, ginsenoside Rg1, ginsenoside Rb1, β-asarone, and α-asarone are identified as potential active ingredients of KXS for anti-AD effects.DiscussionThese findings provide an experimental basis for developing new drugs based on KXS and its active ingredient combinations.